Ecological Citizenship: Habitus of Care in the Public Sphere - Bartkienė, Aistė; Bikauskaitė, Renata; Šaulauskas, Marius Povilas (Problemos, 2018)
[full article, abstract in English; only abstract in Lithuanian] While scholars and popular writers often stress individual responsibility as a way of saving nature, there is a growing understanding that “doing one’s bit” may not be enough to address local and global environmental issues. Focusing on the concept of ecological citizenship as a starting point, our paper seeks to explore the concept of ecological citizenship and show how individualized experiences and socially and culturally embedded practices of care for the environment relate to civic engagement. We connect ecological citizenship with the ethics of care and Pierre Bourdieu’s concept of habitus, which links individual experience of embodied care for environment with broader political and social issues. We argue that the perspective of the ethics of care informed by the concept of habitus broadens the concept of ecological citizenship by, on the one hand, highlighting the rational responsibility to care, and, on the other hand, by revealing how affect-based ties to the environment and established habits of caring are cultivated in local communities. Ecological citizenship based on the habitus of care can be seen as exercised in participation in the public sphere and also through caring practices where public and private fields overlap.